PEMBERDAYAAN GURU TAHFIZ MELALUI PENGENALAN METODE-METODE TAHFIZ AL-QUR'AN DI SEKOLAH TINGGI AGAMA ISLAM SUNAN PANDANARAN YOGYAKARTA - Siti Khodijah (LPPM Universitas Al Muslim, 2025)
Memorizing the Qur'an is increasingly in demand from various sectors, even in schooling, in the pesantren system and boarding schools also organize the tahfiz Al-Qur'an program. Some institutions have special methods in achieving the target quantity of memorization as well as to strengthen memorization. However, not all methods offered are suitable for all individuals, there are even some students who have reached a large quantity of memorization who have not found a method that suits the learning style and mood of the Qur'an memorizer. The purpose of this community service activity was to provide insight to tahfiz teachers and prospective tahfiz teachers about the tahfiz method that has developed to accommodate the diversity of individuals in the process of acquiring and strengthening memorization. Through the implementation of active learning and the ‘everyone is teacher here’ strategy, the introduction of the tahfiz method received a positive response. This can be seen in this activity, students who have become badal tahfiz have the experience to practice the tahfiz teaching method and were ready to do enrichment and empowerment method of Al-Quran memorization and allocate spare time to provide assistance to students who memorize the Qur'an in implementing their chosen methods.